Research on investment-return model of new power system considering financial pressure - Jun Zhang; Chi Wu; Gonglin Wang; Jiao Du; Yongbiao Yang (Energy Reports, 2023)
The investment-return model of power system plays an important part in the business model of power system. In previous studies, the financial pressure brought by the proportion of power project investment was neglected. An investment-return model based on asymmetric Nash bargaining was proposed in this paper, which could better reflect the game process of investment-return in the new power system. Firstly, the stakeholders of cooperative game were analyzed so as to establish the framework of cooperative game model. Secondly, combined with various characteristics of new power system, various influencing factors of the cooperative game was estimated. Thirdly, the expression and solution of Nash bargain were put forward. Finally, the availability of the model was verified by an example. The experiment showed that the investment-return model could reflect the process of investment-return of the new power system more completely.